Isomorphie bzw. Nichtisomorphie in der rezeptiven Verarbeitung zweitsprachlicher Äußerungen - Figas, Janusz (Studia Germanica Posnaniensia, 2018)
In this paper the author discusses differences between a skilful and less skilful second language speech recognition. As an exponent in the evaluation of the quality of linguistic perception the author adopts the material from echoic reproduction, in this case these are the results of dictation. This material provides proof (evidence) of numerous morphological and syntactic deformations and in the meantime the number of the so called spelling mistakes is small. In order to diminish the scale of these problems the second language learner should achieve full isomorphy of perception just in these fragments in which the defect appeared spontaneously.